Under pressure: Psychological perspectives on letterpress, craft and well-being. Issue 1 (1st March 2020) - Squire, Victoria; Homer, Sophie R.
AbstractArts and crafts are widely considered to be psychologically beneficial. Letterpress, as a traditional method of printing, was made redundant by computers in the later twentieth century but has enjoyed a 'rebirth' in recent years. There are a growing number of independent presses, and universities who are recognizing its potential as a pedagogical tool. As a printing method, it is no longer a necessity, so what is its role going forward? The techniques are not lost, but their value has changed. As a craft, letterpress has several distinctive qualities, particularly when compared to digital alternatives. When working with letterpress, students are no longer alone at their desks. Rather, the letterpress workshop is a social, communal space. In this article we reflect on the resurgence of letterpress as a celebration of culture and heritage: a coming together of like-minded individuals in a community of action. What is the value of enabling students to immerse themselves in letterpress, and what are the effects of this immersion on the practitioner and their well-being? There is a shift in focus of letterpress from output ‐ mass-produced printed media ‐ to process. We analyse the unique qualities of this process ‐ its physicality, the restrictions it imposes and the latitude it allows ‐ and explore links to mental and physical health and well-being. This position paper explores the practical, conceptual and emotional dimensions of letterpress as a craft. It draws upon personal reflection, observation and anecdotal accounts collected over years of teaching (V. S.), while offering psychological perspectives on the links between letterpress, craft and well-being (S. R. H.).